Ambient preparation and reactions of gas phase silver cluster cations and anions1. Issue 28 (28th July 2015) - Wleklinski, Michael; Sarkar, Depanjan; Hollerbach, Adam; Pradeep, Thalappil; Cooks, R. Graham
<x xml:space="preserve">Abstract</x> The production and reactivity of silver cluster cations and anions at atmospheric pressure is demonstrated.